Combined therapy with Xuezhikang and low-dose rosuvastatin provides an effective and safe therapeutic strategy for dyslipidemic patients. (June 2015) - Wang, Min; Zhao, Shui-Ping; Tan, Ming-Yue; Huang, Fang
Aims: Double-dose statin regimen achieves merely 6% of decrease in serum LDL cholesterol (LDL-C) levels, whereas the risk of side effects increased largely.Methods: In order to evaluate the lipid lowering effects and safety of combined therapy with Xuezhikang (XZK) and low-dose rosuvastatin, we recruited 30 patients to randomly divide into two groups, and then received combined therapy with XZK at 1.2 g/day and rosuvastatin at 5 mg/day or rosuvastatin at 10 mg/day, respectively. After 8 weeks, the subjects in the two groups cross-changed their treatments for the second period (8 weeks).Results: Compared with rosuvastatin alone, the combined therapy induced a significant decrease in LDL-C, total cholesterol and triglyceride with no serious adverse events, and exerted a slight effect on PCSK9 level.Discussion: The results suggest that combined therapy is a first-line therapeutic strategy for dyslipidemia patients.